Measuring the Mosaic : An Intellectual Biography of John Porter - Helmes-Hayes, Richard C. (Richard Charles), 1951- (Book collections on Project MUSE., 2010)
Measuring the Mosaic is a comprehensive intellectual biography of John Porter (1921-1979), author of The Vertical Mosaic (1965), preeminent Canadian sociologist of his time, and one of Canada's most celebrated scholars.